Investigation of Molten Cobalt Halide/Sodium Metavanadate Mixtures as Redox Catalysts for the Oxidative Coupling of Methane - Claridge, J; Green, M; Lago, R; Tsang, S; York, A (1994)
Molten mixtures of sodium metavanadate and cobalt halide have been tested as catalysts for the activation of methane at 750°C in redox mode. It is found that these melts can convert methane selectively to C2 + products in the absence of molecular oxygen. The initial activity and selectivity of the melt can then be restored after dioxygen treatment. It is also found that the addition of cobalt chloride gives a higher CH4 conversion, C2 + selectivity and C2H4/C2H6 ratio than pure sodium metavanadate. Surprisingly, addition of cobalt bromide shows a similar enhancement. IR and ESR spectra of quenched catalyst samples showed that the cobalt and vanadium ions are reduced by methane and can be reoxidised by dioxygen. © 1994 Elsevier Science B.V. All rights reserved.